Implementasi Pemikiran Tokoh Neo Keynesian Pada Perekonomian Indonesia (JEB17 : Jurnal Ekonomi dan Bisnis, 2024)
Around 1970, there was stagflation that could not be solved using Keynes's framework. Then some economic scientists began to abandon the Keynes theory and the Phillips curve, which is a trade-off between the magnitude of inflation and unemployment, also began to be abandoned in the macroeconomic consensus. The micro foundations of Keynesian thought began to be questioned and New Classical thought began to dominate replacing Keynes's thinking. Keynesian ideas continued to develop and reappeared around 1980 and are often called the New Keynesian Group. It begins with the premise that in the economy there is involuntary and persistent unemployment and economic fluctuations are at the center of all problems in the economy, such as: repression and depression which represent large-scale market failures. The New Keynesians also place reform in the foundations of microeconomics. New Keynesian thought still maintains the Keynesian tradition of rigidity in prices and nominal wages, so the New Keynesians try to find a more acceptable explanation. The views of many scientists such as Alvin Harvey Hansen, Wassily Leontief, Paul Samuelson, Simon Kuznets, and others related to New Keynesianism are still being applied by countries in the world, such as Indonesia. Keywords: neo keynesian, acceptable explanation, persistent unemployment and economic fluctuations